2019
DOI: 10.3390/ijerph16132289
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater Chemistry and Blood Pressure: A Cross-Sectional Study in Bangladesh

Abstract: Background: We assessed the association of groundwater chemicals with systolic blood pressure (SBP) and diastolic blood pressure (DBP). Methods: Blood pressure data for ≥35-year-olds were from the Bangladesh Demographic and Health Survey in 2011. Groundwater chemicals in 3534 well water samples from Bangladesh were measured by the British Geological Survey (BGS) in 1998–1999. Participants who reported groundwater as their primary source of drinking water were assigned chemical measures from the nearest BGS wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Meanwhile, a review of the health impacts of barium spanning from 1875 to 2014 demonstrated that low and moderate doses of Ba caused elevated blood pressure in animal studies [16]. However, there was a null association of Ba concentrations with SBP or DBP levels [42]. In this study, an inverse association between urinary Ba concentrations and blood pressure levels and hypertension risk was found.…”
Section: Discussionmentioning
confidence: 53%
“…Meanwhile, a review of the health impacts of barium spanning from 1875 to 2014 demonstrated that low and moderate doses of Ba caused elevated blood pressure in animal studies [16]. However, there was a null association of Ba concentrations with SBP or DBP levels [42]. In this study, an inverse association between urinary Ba concentrations and blood pressure levels and hypertension risk was found.…”
Section: Discussionmentioning
confidence: 53%
“…The higher cardiometabolic disease risks among the rainwater drinkers compared with coastal groundwater are likely due to reduced intake of Ca, Mg and K. We elsewhere reported that groundwater minerals influence blood pressure of the Bangladeshi population 31 , and the blood pressure-lowering effects of Ca and Mg from drinking water overweighed the blood pressurepromoting effects of Na 32 , which explains the lower blood pressure among groundwater drinkers compared with rainwater drinkers. The findings from this study have likely generalizable implications in other saline-water-affected coastal regions, where rainwater and desalinated water without mineral fortification are being promoted to mitigate water salinity problems.…”
Section: Discussionmentioning
confidence: 92%
“…A study in coastal Bangladesh found drinking mild‐saline water was associated with higher urinary concentrations of calcium, magnesium, and sodium compared to freshwater drinkers (Naser et al, ). Magnesium in groundwater was associated with lower blood pressure of the Bangladeshi population (Naser et al, ). Studies suggest that bioavailability of essential dissolved elements from drinking water is very high (World Health Organization (WHO), ), and some populations in coastal Bangladesh can get up to 50% of their daily calcium and magnesium requirement by drinking 2 L of groundwater (Hoque & Butler, ).…”
Section: Discussionmentioning
confidence: 99%